2018
DOI: 10.30946/2219-4061-2018-8-3-100-111
|View full text |Cite
|
Sign up to set email alerts
|

Modern Approaches to the Surgical Treatment of Biliary Atresia

Abstract: The review of literature deals with the current classification of the biliary atresia, presents the authors’ opinion considering a technique of theKasaiprocedure, and displays modern modifications of portoenteroanastomosis estimating their effectiveness. PubMed database and Google Scholar search system were used to search for primary terms. Survival of children with this pathology was analyzed depending on theKasaitechnique, anatomical form, terms of portoenteroanastomosis and importance of early diagnosis of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
1
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 48 publications
1
1
0
Order By: Relevance
“…The observed correlation of the native liver survival rates with the age at surgery is consistent with the literary data on this subject [11,13,16,19]. For instance, Wang et al demonstrated that Kasai surgery at the age of under 81 days significantly increases native liver life expectancy as compared with the patients operated at a later age [13].…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…The observed correlation of the native liver survival rates with the age at surgery is consistent with the literary data on this subject [11,13,16,19]. For instance, Wang et al demonstrated that Kasai surgery at the age of under 81 days significantly increases native liver life expectancy as compared with the patients operated at a later age [13].…”
Section: Discussionsupporting
confidence: 83%
“…In this study, we assessed the effectiveness of Kasai surgery by post-operative resolution of BA symptoms, age-related complications, and survival rates. According to the published evidence, the effectiveness of Kasai surgery generally varies in the range of 50-95% [10][11][12][13][14][15][16]. In some studies, the effectiveness is assessed by a decrease in bilirubin levels to 2 mg/dL (34.2 µmol/L), which renders the effectiveness of 40% on average [15].…”
Section: Discussionmentioning
confidence: 99%